Concentrations of Fecal Bile Acids in Participants with Functional Gut Disorders and Healthy Controls - James SC; Fraser K; Young W; Heenan PE; Gearry RB; Keenan JI; Talley NJ; Joyce SA; McNabb WC; Roy NC (MDPI (Basel, Switzerland), 2021)
Bile acids are metabolites involved in nutrient absorption and signaling with levels influenced by dietary intake, metabolic processes, and the gut microbiome. We aimed to quantify 23 bile acids in fecal samples to ascertain if concentrations differed between healthy participants and those with functional gut disorders. Fecal bile acids were measured using liquid chromatography-mass spectrometry (LC-MS) in the COMFORT (The Christchurch IBS cohort to investigate mechanisms for gut relief and improved transit) cohort of 250 participants with Rome IV IBS (IBS-constipation (C), IBS-diarrhea (D), IBS-mixed (M)), functional gut disorders (functional constipation (FC), functional diarrhea (FD)) and healthy controls (FC n = 35, FD n = 13, IBS-C n = 24, IBS-D n = 52, IBS-M n = 29, and control n = 97). Dietary information was recorded to ascertain three-day dietary intake before fecal samples were collected. Fecal bile acid concentrations, predominantly primary bile acids, were significantly different between all functional gut disorder participants and healthy controls (CDCA p = 0.011, CA p = 0.003) and between constipation (FC + IBS-C) and diarrhea (FD + IBS-D) groups (CDCA p = 0.001, CA p = 0.0002). Comparison of bile acids between all functional groups showed four metabolites were significantly different, although analysis of combined groups (FC + IBS-C vs. FD + IBS-D) showed that 10 metabolites were significantly different. The bile acid profiles of FD individuals were similar to those with IBS-D, and likewise, those with FC were similar to IBS-C. Individuals with a diarrhea phenotype (FD + IBS-D) had higher concentrations of bile acids compared to those with constipation (FC + IBS-C). Bile acid metabolites distinguish between individuals with functional gut disorders and healthy controls but are similar in constipation (or diarrhea) whether classified as IBS or not.
Keywords: bile acids; functional gut disorder; irritable bowel syndrome; liquid chromatography-mass spectrometry